Combined Orthopaedic and Vascular Injuries With Ischemia: A Multicenter Analysis. Issue 10 (October 2021) - Shahien, Amir A.; Sullivan, Matthew; Firoozabadi, Reza; Lu, Keyin; Cannada, Lisa; Timmel, Mark; Ali, Ashley; Bramlett, Kasey; Marcantonio, Andrew; Flynn, Megan; Vallier, Heather; Nicolay, Rick; et al.
Abstract : Objectives: To review a large, multicenter experience to identify the current salvage and amputation rates of these combined injuries and, where possible, the variables that predict amputation. Design: Retrospective. Setting: Nine trauma centers. Patients: This study involved 199 patients presenting to 9 trauma centers with orthopaedic and vascular injuries resulting in ischemic limbs for whom the orthopaedic service was involved with the decision for salvage versus amputation. Results: We reviewed 199 patients, 17–85 years of age. One hundred seventy-two of the injuries were open. Thirty-eight patients (19%) were treated with amputation upon admission as they were deemed to be unsalvageable. Of the remaining 161 patients who had attempted salvage, 36 (30%) required late amputation. Closed injuries were successfully salvaged in 25 of 27 cases (93%). The highest rate of amputation was in tibia fractures with a combined amputation rate of 62%. In those attempted to be salvaged, 21 of 48 (44%) required amputation. The ischemia time for successful salvage was significantly less, P = 0.03. One hundred twenty-four patients had their definitive vascular repair before the bony reconstruction. There were 15 vascular complications, of which 13 (86%) had the definitive vascular repair performed before the definitive osseous repair, although this was not statistically significant. Conclusions: In this series of combined orthopaedic and vascular injuries, we found a high rate of acute and late amputations. It is possible that other protocols, such as shunting and stabilizing the osseous injury, before vascular repair may benefit limb salvage, although this needs more study. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.